Analysis of the Application of Visitor Management to Visitor Satisfaction at Museum Geologi - Septiyani, Dwi; Chendraningrum, Dinarsiah (Politeknik Negeri Bandung, 2025)
This study examines how the implementation of visitor management influences visitor satisfaction at the Museum Geologi in Bandung, Indonesia. Although visitor management has been widely discussed in the tourism literature, empirical evidence from educational museums in developing countries remains limited. A quantitative descriptive design was employed using a structured questionnaire distributed to 125 visitors. Visitor management was measured through four dimensions—access management, placement of facilities and interpretation, regulation of support facilities, and time and space distribution—while visitor satisfaction was assessed using expectation conformity, revisit intention, and willingness to recommend. Data were analyzed using simple linear regression. The findings reveal that both visitor management and visitor satisfaction are rated highly. Visitor management has a significant and positive influence on visitor satisfaction (R² = 0.666; t = 15.418; p < 0.001). These results emphasize that well-planned visitor management enhances visitor experience and satisfaction, particularly through efficient access systems and clear spatial guidance. The study contributes to the growing discourse on sustainable and inclusive visitor management practices in public educational attractions. Managerially, the findings suggest that museums should adopt integrated digital systems and inclusive accessibility design to improve visitor satisfaction and ensure long-term sustainability.